Neuronal regeneration in a zebrafish model of adult brain injury - Norihito Kishimoto; Kohei Shimizu; Kazunobu Sawamoto (The Company of Biologists, 2012)
SUMMARY Neural stem cells in the subventricular zone (SVZ) of the adult mammalian forebrain are a potential source of neurons for neural tissue repair after brain insults such as ischemic stroke and traumatic brain injury (TBI). Recent studies show that neurogenesis in the ventricular zone (VZ) of the adult zebrafish telencephalon has features in common with neurogenesis in the adult mammalian SVZ. Here, we established a zebrafish model to study injury-induced neurogenesis in the adult brain. We show that the adult zebrafish brain possesses a remarkable capacity for neuronal regeneration. Telencephalon injury prompted the proliferation of neuronal precursor cells (NPCs) in the VZ of the injured hemisphere, compared with in the contralateral hemisphere. The distribution of NPCs, viewed by BrdU labeling and ngn1-promoter-driven GFP, suggested that they migrated laterally and reached the injury site via the subpallium and pallium. The number of NPCs reaching the injury site significantly decreased when the fish were treated with an inhibitor of γ-secretase, a component of the Notch signaling pathway, suggesting that injury-induced neurogenesis mechanisms are at least partly conserved between fish and mammals. The injury-induced NPCs differentiated into mature neurons in the regions surrounding the injury site within a week after the injury. Most of these cells expressed T-box brain protein (Tbr1), suggesting they had adopted the normal neuronal fate in this region. These results suggest that the telencephalic VZ contributes to neural tissue recovery following telencephalic injury in the adult zebrafish, and that the adult zebrafish is a useful model for regenerative medicine.